Metabolomic Profiling of Red Blood Cells to Identify Molecular Markers of Methotrexate Response in the Collagen Induced Arthritis Mouse Model - Yezan M. Salamoun; Kishore Polireddy; Yu Kyoung Cho; Ryan Sol Funk (MDPI AG, 2022)
Although methotrexate (MTX) is the first line disease-modifying therapy used in the treatment of autoimmune arthritis, it is limited by its unpredictable and variable response profile and lack of therapeutic biomarkers to predict or monitor therapeutic response. The purpose of this work is to evaluate the utility of red blood cell (RBC) metabolite profiles to screen for molecular biomarkers associated with MTX response. Methods: Utilizing the collagen-induced arthritis mouse model, DBA/1J mice were treated with subcutaneous MTX (20 mg/kg/week) and RBC samples were collected and analyzed by semi-targeted global metabolomic profiling and analyzed by univariate analysis. Results: MTX treatment normalized the following RBC metabolite levels that were found to be altered by disease induction: N-methylisoleucine, nudifloramide, phenylacetylglycine, 1-methyl-L-histidine, PC 42:1, PE 36:4e, PC 42:3, PE 36:4e (16:0e/20:4), and SM d34:0. Changes in the RBC metabolome weakly but significantly correlated with changes in the plasma metabolome following MTX treatment (ρ = 0.24, p = 1.1 × 10−13). The RBC metabolome resulted in the detection of nine significant discriminatory biomarkers, whereas the plasma metabolome resulted in two. Overall, the RBC metabolome yielded more highly sensitive and specific biomarkers of MTX response compared to the plasma metabolome. N-methylisoleucine was found to be highly discriminatory in both plasma and RBCs. Conclusions: Our results suggest that RBCs represent a promising biological matrix for metabolomics and future studies should consider the RBC metabolome in their biomarker discovery strategy.